Analysis of Malaria Transmission Dynamics at Borobudur Health Center, Magelang Regency (Case Study 2021-2022) - Naila Afnaniya; Aris Santjaka; Bahri Bahri (JURNAL KESEHATAN LINGKUNGAN, 2023)
Introduction: Magelang District received a malaria elimination certificate in 2014. No cases found at Borobudur Health Center since 2009 but in October 2021, there was a spike in the number of patients, with 38 instances spread across Giripurno Village, Giritengah Village, and Majaksingi Village. Therefore, it is necessary to study the dynamics of malaria transmission so that the methods of malaria transmission are known to prevent extraordinary malaria cases. Methods: This is qualitative research with a phenomenological approach. This study was conducted in 2023 by reviewing cases from 2021–2022. The respondents in this study included 38 people with malaria. This research uses descriptive analysis assisted by GIS applications to determine the distribution of malaria cases. Results and Discussion: Data processing results for 38 respondents in three villages revealed 23 index cases. Of the 23 cases, nine were within a radius of no more than 400 m and occurred within three days, thus including cluster classification. Theoretically, the same vector transmits it and has a high vectorial capacity. The other 15 patients were suspected to have secondary cases, with two transferred from the first case. The results of the breeding place survey or the potential breeding place after rearing revealed the species Anopheles balabacensis. Other predictors of malaria transmission are optimal temperature and humidity, environment, livestock places to rest mosquitoes, and patient behavior that causes a high frequency of mosquitoes biting humans. Conclusion: In this case, the transmission model was a cluster, and 100% of the cases were indigenous.